Unveiling the secret pollinators: A deep dive into moringas’ pollination ecology - Saravanan , P A; Ravichandran , V; Veeramani , P; Velmurugan, M; Jayakumar, J; Alagar, M (Plant Science Today, 2025)
A famous vegetable crop in India that is rich in nutrients and heavily dependent on bees for pollination is moringa. A survey was taken in the Karur and Perambalur districts of Tamil Nadu to document the diversity of pollinators and insect visitors of moringa. The observations were analyzed using diversity indices. According to the studies, 13 hymenopteran, 7 dipteran, and 7 lepidopteran insects visited moringa plants. Fruit set and quality are maximized in moringa when pollination is successful. Therefore, four treatments have been applied to the Asiatic hive bee, Apis cerana indica, to explore the pollination capability and the foraging ecology of other key bee pollinators of moringa. The results affirmed that the significant Apis pollinators spend more time on nectar collection than pollen gathering. The peak foraging activity of Apis pollinators happened in the morning hours during 0900 -1100h. A. cerana indica and A. dorsata commence their foraging activity much earlier in the morning than A. florea. The foraging activity gradually declined after 1400h. The abundance of A. cerana indica was very high in managed bee pollination plots compared to open pollination plots. The managed bee pollination plots (128.2 fruits/tree) recorded 19.14 percent more fruit sets and 11.40 % more fruit yield than open pollination plots (107.6 fruits/tree) by deploying four Asian bee colonies per acre of moringa crop.